Propagation of guided waves in a fluid layer bounded by two viscoelastic transversely isotropic solids - Ashour, Ahmed S (Elsevier Science Publishers B.V., Amsterdam, Netherlands, 2000)
The analysis of Stoneley wave propagation in a fracture is essential for the identification and evaluation of fracture parameters from the borehole Stoneley wave. Also, it is important for many geophysics considerations, e.g. for tremor and long-period events observed in volcanoes and geothermal areas. In this paper, we investigate the guided waves propagation in a fluid layer lying between two viscoelastic vertically transversely isotropic media. The viscoelastic mechanism models the attenuation due to the presence of fluid saturation in the rock. A model based on the superposition of three inhomogeneous partial plane waves: one in the fluid and two heterogeneous waves in the solid is developed. The dispersion equation is obtained for this case. A numerical solution is carried out to obtain the guided wave velocity and attenuation coefficient. The results of this investigation show that there is a strong correlation between the velocity dispersion and attenuation of Stoneley wave and the anisotropic parameters of the medium especially in a sandstone fast. medium. q2000 Elsevier Science B.V. All rights reserved.